Evaluation of Lysine, Methionine and Threonine Needs of Broilers Three to Six Week of Age under Moderate Temperature Stress - Ojano-Dirain, C.P.; Waldroup, P.W. (International Journal of Poultry Science, 2001)
Information on amino acid requirements of broilers raised under warm environments is very limited. Two studies of identical design were conducted to evaluate Lys, Met and Thr needs of 3 to 6 week-old male broilers held in battery pens at 26.7 oC. A basal diet was supplemented with amino acids in a 4 x 3 x 2 factorial arrangement with Lys levels of 1.03, 1.08, 1.12, and 1.16%, Met levels of 0.38, 0.44, and 0.50%, and Thr levels of 0.78 and 0.87%. Feed consumption, body weight (BW) gain and carcass yield were determined. Lys levels had no significant effect on 21 to 42 d BW gain, feed conversion ratio (FCR), or dressing percentage (DP). Increasing Lys levels from 1.03 to 1.12% significantly (P < 0.05) improved breast yield (BY) and reduced abdominal fat. Increasing Met to 0.44% resulted in significant improvements in BW gain, FCR, DP, BY, and a numerical (P=0.08) reduction in AF. Threonine levels used in this study had no significant effect on any parameter. There was a significant interaction of Lys and Thr on breast yield; however it followed no consistent trend. These results suggest that under moderate heat stress, the present levels of Lys and Met suggested by NRC may be inadequate for maximum live performance or breast meat yield; however, suggested levels of Thr appear to be adequate for this age period.